Sexual Assault and Sexual Harassment in the U.S. Military Top-Line Estimates for Active-Duty Service Members from the 2014 RAND Military Workplace Study - Morral, Andrew R. (RAND Corporation, 2014)
In early 2014, the Department of Defense Sexual Assault Prevention and Response Office asked the RAND Corporation to conduct an independent assessment of sexual assault, sexual harassment, and gender discrimination in the military. This report provides initial top-line estimates from the resulting RAND Military Workplace Study, which invited close to 560,000 service members to participate in a survey fielded in August and September of 2014.